Comparative analysis of fat composition in marrow, serum, and muscle from aging C57BL6 mice. (September 2022) - Al Saedi, Ahmed; Wang, Zhiying; Shah, Anup; Brotto, Marco; Duque, Gustavo
Abstract: Osteosarcopenia is an age-related condition characterized by fragile bone and low muscle mass and function. Fat infiltration concomitantly contributes to age-related bone and muscle decline. Fat-secreted factors could be locally secreted in the muscle and bone marrow milieu affecting cell function and survival. However, the specific fat-related secretory factors that may simultaneously affect those tissues remain unknown. Using targeted-lipidomics approach, we comprehensively quantified fat composition (lipid mediators [LMs]) in bone marrow flush, gastrocnemius and serum obtained from 6-, 24- and 42-week-old C57BL6 mice. Compared to young mice (6wks), all tissues in older mice showed significantly higher levels of arachidonic acid (AA) and AA-derived eicosanoids, PGA 2, TXB 2, and 11, 12-EET, which are known to affect muscle and bone function. Moreover, Lipoxin B4, another AA product and an enhancer of bone turnover and negative regulator for muscle, showed significantly lower values in older mice compared to young mice in both genders. Furthermore, eicosapentaenoic acid and docosahexaenoic acid autoxidation products (20-HDoHE, 11-HDoHE, 7-HDoHE and 4-HDoHE), and omega-3 fatty acids that negatively regulate bone and muscle health, were significantly higher in older mice. In conclusion, these results suggest that LMs could play a role in modulating musculoskeletal function during aging. Highlights: Lipid mediators have a unique profile in aging muscle and bone. There is valuable evidence on the role of fat infiltration in osteosarcopenia. Older mice showed significantly higher levels of lipid mediators compared to young mice. Lipid mediators could play a role in modulating musculoskeletal function during aging.